The Eisenhower presidency, 1953-1961 - Damms, Richard V. (Seminar studies in history., 2002)
"Drawing on the expanding documentary record and the most recent scholarship, this book provides students with a valuable, up-to-date synthesis of the Eisenhower presidency."--Jacket